The Effect of Self-Concept, Copywriting and Sales Promotion On Impulse Buying and Its Implications On Digital Repurchase Intention of Healthy Food and Beverage Products In Z Generation: (Empirical Study On Private Universities of Management Study Programs In East Jakarta, Central Jakarta, South Jakarta and West Jakarta) - Dewi Nurbaiti; Yudi Yulius; Nandan Limakrisna (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to analyze and prove the influence of Self-Concept, Copywriting, Sales Promotion on Impulse Buying both partially and simultaneously, as well as the influence of Self-Concept, Copywriting, Sales Promotion, Impulse Buying on Repurchase Intention both partially and simultaneously. The research method used in this study is a descriptive survey method and an explanatory survey with a sample size of 394 respondents, and the data analysis method used is SEM (Structural Equation Modelling). Based on the results of the study, the following findings were obtained, namely Self-Concept has a positive and significant effect on Impulse Buying. Copywriting has a positive and significant effect on Impulse Buying. Sales Promotion has a positive and significant effect on Impulse Buying. Self-Concept, Copywriting and Sales Promotion together have a positive and significant effect on Impulse Buying with a contribution of 85%. However, when viewed partially, self-cocept has a dominant influence on Impulse Buying. Self-Concept has a positive but not significant effect on Repurchase Intention, Impulse Buying has a positive and significant effect on Repurchase Intention, Sales Promotion has a positive and significant effect on Repurchase Intention, Impulse Buying has a positive and significant effect on Repurchase Intention. Self-Concept, Copywriting, Sales Promotion and Impulse Buying together have a positive and significant effect on Repurchase Intention with a contribution of 80%. However, when viewed partially, Sales Promotion most dominantly affects Repurchase Intention. Also for Self-Concept, Copywriting and Sales Promotion, Impulse Buying has a role as partial mediating to Repurchase Intention. This research found and proved that to increase Impulse Buying and Repurchase Intention, it is necessary to create advertisements that can affect the Self-Concept of generation Z and also improve Sales Promotion programs.